Fatores clínicos associados a fistula liquórica cutânea em lactentes operados de derivação ventriculoperitoneal - Andrea Silva de Pinho (2011)
Introduction: The ventriculoperitoneal shunt for hydrocephalus treatmentassociates itself to the post-operated complications and infection is the most important. The cerebrospinal fluid wound leakage increases to 27 times this indicative. The clinical observance suggests that this complication occurs to higher frequency with children preterm and underweight. Objectives: Determine clinical factors and of fetal maturity which can be involved in development of post operated cerebrospinal fluid wound leakage. Methodology: They were evaluated 72 lactents submitted to a ventriculoperitoneal shunt in Odilon Behrens Municipal Hospital from 2004 to 2008. All the children were treated by the same surgeon and the clinical data and laboratorial to birth and to the surgery collected to the patient records and notes in their own protocols. Result: There was a trend to an occurrence of cerebrospinal fluid wound leakage in children birth with weight percentile under 10 (p = 0.06) and a higher incidence in operated children before 1 month of life (p<0.05). The other parameters were not significant. Conclusion: The chronological age and the level of nutrition intra uterus are determinant factors in wound healing of newborns, having impact in incidence of complications in wound of lactents submitted to ventriculoperitoneal shunt.